2007
DOI: 10.1055/s-2006-924296
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Physical Activity, Physical Fitness and Heart Rate Variability in Preadolescents

Abstract: The amount and type of physical activity (PA) appropriate in youth for optimal health is still being discussed. The purpose of this study on 12-year-old preadolescents is to evaluate the association of two PA patterns, corresponding to different exercise intensities, with some health-related indexes. PA was evaluated by triaxial accelerometry in 67 student subjects, who were successively classified according to 1) their usual participation or not in moderately intense (> 4 metabolic equivalents, METs) activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 33 publications
3
48
1
1
Order By: Relevance
“…Ara et al 18 showed in 114 prepubertal boys (9.4±1.5 years) that participation in at least 3 hours per week of extracurricular physical activities and sport competitions was associated with higher squat jump performance and lower fat mass levels compared with non-participants. In contrast, Buchheit et al 33 showed no association between PA measured by accelerometry and counter movement jump test in a sample of 67 preadolescents. Foo et al 34 Regardless of the evident gender differences, our results do not show any relationship between PA and fat free mass, and suggest that after controlling for the fat free mass, vigorous PA is the minimum physical stimulus able to enhance muscular strength.…”
Section: Discussionmentioning
confidence: 83%
“…Ara et al 18 showed in 114 prepubertal boys (9.4±1.5 years) that participation in at least 3 hours per week of extracurricular physical activities and sport competitions was associated with higher squat jump performance and lower fat mass levels compared with non-participants. In contrast, Buchheit et al 33 showed no association between PA measured by accelerometry and counter movement jump test in a sample of 67 preadolescents. Foo et al 34 Regardless of the evident gender differences, our results do not show any relationship between PA and fat free mass, and suggest that after controlling for the fat free mass, vigorous PA is the minimum physical stimulus able to enhance muscular strength.…”
Section: Discussionmentioning
confidence: 83%
“…The high physical activity level of adolescents provides health benefits, and it may also have a role in improving educational skills and well-being [12]. Previous studies have further shown that endurance training of prepubertal healthy children has a positive effect on aerobic potential, morphological parameters and functional cardiac parameters [3]. Being already physically active and the short training period in the test group could explain why their skeletal muscle mass did not change.…”
Section: Discussionmentioning
confidence: 98%
“…The acute effects of physical training and exercise on cardiac autonomic activity in young healthy participants [2,4,6] and in children with a pre-existing condition such as obesity [14] have been reported. In a meta-analysis of randomized controlled trials in healthy children, da Silva et al [5] found no effect of exercise training on HRV.…”
Section: Introductionmentioning
confidence: 99%
“…The wide possibilities for using HRV added to the ease of data acquisition enables its use for the identification of ANS-related phenomena in individuals of different ages and states of health, as well as making evaluation possible in individuals during rest or exercise (1,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%